Pemanfaatan Klasifikasi Soal Biologi Cognitive Domain Bloom’s Taxonomy Menggunakan KNN Chi-Square Sebagai Penyusunan Naskah Soal - Indah Listiowarni; Nindian Puspa Dewi (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2020)
The question manuscript is a document that contains a collection of exam questions that are commonly used by an educator to test the absorption of their students on the material that has been presented in class. Question manuscripts made by educators are made based on a pre-made question grid, and contain a certain percentage of each cognitive domain category in the bloom taxonomy. The level in the bloom taxonomic cognitive domain describes the level of difficulty of each item made, so that an educator must first make a formula in a planning script called a question grid. The items that have been classified based on the cognitive domain taxonomic level of bloom using the KNN classifier method and the Chi-square feature selection are proven to be the right combination, the classification results of these items will be used for the preparation of a text for exam questions with an adjusted percentage formula. With the question grid that has been made beforehand, it is hoped that this research can be used to facilitate educators in drafting appropriate exam questions for their students